Using a disposable platform based on reduced graphene oxide, iron nanoparticles and molecularly imprinted polymer for voltammetric determination of vanillic acid in fruit peels - Buffon, Edervaldo [UNESP] (2022)
This work reports the development and application of a disposable electrochemical platform for vanillic acid (VA) detection using screen-printed electrode modified with reduced graphene oxide, iron nanoparticles and molecularly imprinted poly(pyrrole) film. The electrochemical platform was characterized by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. Using optimized conditions, the proposed disposable platform presented linear concentration ranges of 1.0 × 10−9 to 1.5 × 10−7 mol/L. The limits of detection and quantification obtained for the device were 3.1 × 10−10 and 1.0 × 10−9 mol/L, respectively. The electrochemical platform was found to be selective for VA recognition and presented voltammetric responses with good repeatability and stability. The analytical methodology developed was applied for VA determination in banana and orange peels. The results obtained showed that the proposed electrochemical platform has a good accuracy when applied for the determination of VA.